Analisis Perbedaan Tarif Rumah Sakit dan Tarif INA-CBG’s Pelayanan Rawat Inap Salah Satu Rumah Sakit Pemerintah Tipe C Tahun 2021 - Melviani; Rivai Endra Dwi Yulianto; Riswati Ruslan (Jurnal Pharmacopoeia, 2025)
Indonesian Case Base Groups (INA-CBG) become a reference for the Social Security Administering Body (BPJS) in payment of claims at advanced health facilities. From the article search, 20 articles were found that compare the real rates with the INA CBGs rates. Five articles yield higher INA CBG rates than hospital rates and another 15 articles provide higher real rates than INA CBG rates. RS. X is one of the hospitals located outside Java. This study aims to obtain an overview of the comparison between real rates and INA CBGs rates in hospitals. X, diseases with catastrophic or non-catastrophic categories that are widely used in hospitals. X and the comparison of costs and the effect of length of stay on real costs. This study is a cross-sectional study using secondary data, namely BPJS claim data for inpatients at the hospital. X in Southeast Sulawesi in 2021. The distribution normality test uses the Kolmogorov Smirnov normality test. Data with normal distribution were tested for significance using an independent t-test. Data that were not normally distributed were tested for significance with Mann Whitney. There are 2,534 data claimed by RS. X to BPJS in 2021. Claims consist of 209 types of disease descriptions where claims for non-catastrophic diseases are more than claims for catastrophic diseases. The biggest claim was cesarean section (mild) which was 209 claims (8.2%) which was included in the non-catastrophic category. RS. X must spend IDR 1,411,298,920,- to cover the difference between the INA CBGs tariff and the real rate for the non-catastrophic category and IDR 6,878,400 for catastrophic diseases. A stronger correlation between length of stay and real rates indicates that length of stay is one of the factors that cause real rates to be higher than INA CBG rates. The results of the t-test on non-catastrophic diseases showed that nine out of 10 disease descriptions had significant differences for real rates and INA CBG rates, while for catastrophic diseases there were no significant differences. There is only one disease description that has no significant difference, namely a disease with a description of Antepartum Disorder (Mild). The non-catastrophic disease is the most common in hospitalized patients. X in Southeast Sulawesi. The cost of hospital claims is greater than the cost of claims for INA CBGs in non-catastrophic and catastrophic diseases. Length of hospitalization has a significant correlation in hospitalized patients with catastrophic and non-catastrophic diseases. The correlation between length of stay was greater in patients with the catastrophic disease.